A RARE CASE OF COMBINED OVIDUCTAL ADENOCARCINOMA AND LEIOMYOMA IN A WHITE LEGHORN CHICKEN - K. Thilagavathi; J. Selvaraj (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A rare case of combined oviductal adenocarcinoma and leiomyoma in a white leghorn chicken is reported. Necropsy of an adult female white leghorn chicken, showed distension of oviduct. The oviduct serosa revealed small nodules of about 3 mm diameter and the lumen contained brownish exudates. The oviductal mucosa showed irregular nodules of about 0.5 to 1.5 cm in diameter attached to the mucosa of the magnum. Grossly, the mucosal nodules were firm and pink to grey in colour and serosal nodules were grey white in colour. Histopathologically, oviduct mucosal nodule revealed acinar or tubular pattern of tumour cells separated by fibrous tissue. The oviduct serosal nodule revealed interlacing bundles of smooth muscles cells in various directions. Based on histopathological characteristics, the present case was diagnosed as a rare combined case of oviduct adenocarcinoma and leiomyoma in a white leghorn layer chicken.